Spinach Effects (Amaranthus hybridus) on Spatial Memory - Leonita, Intan; Utami, Novi Vicahyani; Wibisono, Yusuf (Althea Medical Journal, 2015)
Â Â Background: Spatial memory reduction in elderly is predicted to increase up to twice every 20 years. Spinach (Amaranthus hybridus) is widely consumed by Indonesian people and is believed to prevent declined spatial memory function. The aim of this study was to determine the effects of spinach on spatial memory in wistar rat induced by diazepam Methods: An experimental study was conducted during the period of October to November 2012 in Pharmacology and Therapy Laboratory, Faculty of Medicine, Universitas Padjadjaran. Twenty five wistar rats were divided into 5 groups; two groups as controls, and 3 groups were given 100, 200, and 400mg/kg BW ethanolic extract of spinach (EESL), respectively. On day 7, group 3, 4, and 5 were given 1 mg/kg BW diazepam injection. Morris water maze tests and calculations of escape latency time (ELT) were performed on day 7 and 8. Data were analyzed using analysis of variance (ANOVA) and least significance difference (LSD) test. Results: On day 7, group 2 experienced acceleration in ELT compared to group 4 and group 5. On day 8, group 2 experienced acceleration in ELT compared to group 3 and group 4. There was no significant increase in spatial memory in group 5 (EESL 400mg/kg BW) that due to the use of higher dosage does not always show better results. Conclusions: EESL can prevent impairment of spatial memory with an effective dose of 200 mg/kg BW.Keywords: Amaranthus hybridus, diazepam, spatial memory, spinach DOI: 10.15850/amj.v2n1.439Â